Beyond Sharing Unpleasant Affect—Evidence for Pain-Specific Opioidergic Modulation of Empathy for Pain. (18th January 2021) - Rütgen, Markus; Wirth, Eva-Maria; Riečanský, Igor; Hummer, Allan; Windischberger, Christian; Petrovic, Predrag; Silani, Giorgia; Lamm, Claus
Abstract: It is not known how specific the neural mechanisms underpinning empathy for different domains are. In the present study, we set out to test whether shared neural representations between first-hand pain and empathy for pain are pain-specific or extend to empathy for unpleasant affective touch as well. Using functional magnetic resonance imaging and psychopharmacological experiments, we investigated if placebo analgesia reduces first-hand and empathic experiences of affective touch, and compared them with the effects on pain. Placebo analgesia also affected the first-hand and empathic experience of unpleasant touch, implicating domain-general effects. However, and in contrast to pain and pain empathy, administering an opioid antagonist did not block these effects. Moreover, placebo analgesia reduced neural activity related to both modalities in the bilateral insular cortex, while it specifically modulated activity in the anterior midcingulate cortex for pain and pain empathy. These findings provide causal evidence that one of the major neurochemical systems for pain regulation is involved in pain empathy, and crucially substantiates the role of shared representations in empathy.